ผลของการใช้เทคนิคการเรียนการสอนแบบสืบเสาะหาความรู้ บูรณาการ เทคโนโลยีสารสนเทศ รายวิชาการออกแบบระบบคอมพิวเตอร์เพื่อการศึกษา - Na Songkhla, sirichaichan (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
The purposes of this study is 1) to study the results of Information Technology using Integrated Teaching-Learning Technique inquiries for Computer System Design for Education 2) to investigate learning achievement of the students in designing computer systems for education, and 3) to determine the satisfaction level of second year students learning Computer System Design for Education. Population used in this study was 30 students, who were studying in the second year of Computer System Design for Education in academic year 2015 at Phranakhon Rajabhat University. The instruments used in this study were plan for Computer System Design for Education, test achievement, and questionnaires on the satisfaction with learning techniques of teaching a quest for knowledge integration technology. Data were analyzed by using mean, and standard deviation The findings of the study are: 1) Results of teaching technique on a quest for knowledge integration technology, Computer System Design for Education, found that the quest for knowledge and integration of information technology was good as measured by achievement. The results of the study were at an average of 84.83 percent. 2) Students’ satisfaction with learning by using teaching techniques on a quest for knowledge integration technology, Computer System Design for Education, was at a good level (μ = 4.04, σ = 0.52).